Tree-dwelling wolves: a new arboreal Hogna species (Araneae: Lycosidae) from Taiwan - Lo, Ying-Yuan; Wei, Chi; Cheng, Ren-Chung (Zootaxa, 2023)
Hogna Simon, 1885 is one of the most diverse genera of wolf spiders, with species that are almost exclusively ground-dwellers. A recent discovery of a tree-hole-living species in Taiwan was therefore surprising. Here, we describe Hogna arborea sp. nov. using a combination of morphological and molecular taxonomic evidence. We also discuss the arboreal lifestyle of this new species and emphasize the need for more detailed ecological research to assess its conservation status.